Hygiene Prevention in Clay Based Ceramic Tiles by Using the Phosphate Extracted from the Mines of Morocco and Its Effect on Technical Properties - Boutaleb, Fatimazahra; Boutaleb, Nadia; Bahlaouan, Bouchaib; Hadidi, Meryem; Benjelloun, Ghita Radi; Louanjli, Fatima Azzahra; Doublali, Fatima Ezzahra; El Antri, Said (European Scientific Journal, ESJ, 2023)
This study offers a simple solution to manufacture ceramic tiles with good technical and hygienic properties in accordance with the ISO standards by integrating phosphate products into the formulation. For phosphate products, three grades were studied: HG-high grade, MG-medium grade and LG-low grade. It has shown, for ceramic tiles generated by dry pressing process and which contain these additives, that there is both an effect of the concentration and the nature of additive on technical and hygienic properties. Mechanical property was improved when the incorporate component is richer in P2O5. Only the use of HG-high grade and MG-medium grade as an additive at least 15% makes it possible to satisfy the mechanical requirement. The anti-biofilm effect of the natural phosphate (PN) as additives to manufacture ceramic tiles has been proven, it may prevent the bio adhesion and the biofilm formation by a percentage, which can reach up to at 75% for the HG-high grade and MG-medium grade. This solution could interest professionals and all users who care about the state of hygiene of their ceramic materials sensible to the formation of biofilm, like orthopedic implants, swimming pool tile…etc